(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
This article is devoted to the study of the history of Samarkand glassmaking. Glass products have been found in the Afrosiyab area since the II century BC. In ancient and early medieval layers, glass beads, medallions and vessels were found from tombs and monuments. From the 8th century, the use of glass products on the same level as pottery means that there were many glassware makers and workshops. One of the earliest workshops in Turkestan was also recorded in Afrosiyab region